Emergence of NDM-1 and OXA-72 producing Acinetobacter pittii clinical isolates in Lebanon. (July 2016) - Al Atrouni, A.; Joly-Guillou, M.-L.; Hamze, M.; Kempf, M.
Abstract: Acinetobacter spp. have emerged as global opportunistic pathogen causing a wide range of infections. Emergence of carbapenem resistance in these organisms is a matter of great concern. We report here the first detection of Acinetobacter pittii clinical isolates in Lebanon carrying either the bla NDM-1 or the bla OXA-72 gene.